Precarity and the Development of Research Careers in Academia - Cairns, D. (2025)
Precarity is a concern that affects researchers in academia across the world. Despite being experienced and highly qualified, many endure working conditions more traditionally associated with people lacking skills and credentials. This book explores this perverse situation, focusing on Portugal, with a view to explaining how precarity starts and then continues for the entire duration of a research career. Using 100 interviews conducted with researchers from across Portugal in 2022-2023, covering a wide range of scientific fields, the book gives these people the opportunity to explain why they became researchers and how they have coped with precarity during the early career stages, and at intermediate and advanced levels. As a sociological study, the book draws on the theoretical concepts of ambivalence, liminality and cruel optimism to help map the parameters of precarity, while the evidence demonstrates its often visceral personal and professional impacts, reaching the conclusion that believing research needs to be a precarious profession must be challenged within higher education institutions and at policy level.